Growth behaviour and mechanical properties of PLL/HA multilayer films studied by AFM - Üzüm, Cagri; Hellwig, Johannes; Madaboosi, Narayanan; Volodkin, Dmitry; von Klitzing, Regine (Beilstein Journal of Nanotechnology, 2012)
Scanning- and colloidal-probe atomic force microscopy were used to study the mechanical properties of poly(L-lysine)/hyaluronan (PLL/HA)n films as a function of indentation velocity and the number of polymer deposition steps n. The film thickness was determined by two independent AFM-based methods: scratch-and-scan and newly developed full-indentation. The advantages and disadvantages of both methods are highlighted, and error minimization techniques in elasticity measurements are addressed. It was found that the film thickness increases linearly with the bilayer number n, ranging between 400 and 7500 nm for n = 12 and 96, respectively. The apparent Young’s modulus E ranges between 15 and 40 kPa and does not depend on the indenter size or the film bilayer number n. Stress relaxation measurements show that PLL/HA films have a viscoelastic behaviour, regardless of their thickness. If indentation is performed several times at the same lateral position on the film, a viscous/plastic deformation takes place.
Keywords: atomic force microscopy; polyelectrolyte multilayers; stress relaxation; viscoelasticity; Young’s modulus

(untitled) - Decher, G.; Hong, J. D.; Schmitt, J. (Thin Solid Films, 1992)

(untitled) - Decher, G. (Science, 1997)

(untitled) - Engler, A. J.; Richert, L.; Wong, J. Y.; Picart, C.; Discher, D. E. (Surf. Sci., 2004)

(untitled) - Richert, L.; Engler, A. J.; Discher, D. E.; Picart, C. (Biomacromolecules, 2004)

(untitled) - Francius, G.; Hemmerlé, J.; Ohayon, J.; Schaaf, P.; Voegel, J.-C.; Picart, C.; Senger, B. (Microsc. Res. Tech., 2006)

(untitled) - Richert, L.; Boulmedais, F.; Lavalle, P.; Mutterer, J.; Ferreux, E.; Decher, G.; Schaaf, P.; Voegel, J.-C.; Picart, C. (Biomacromolecules, 2004)

(untitled) - Schneider, A.; Francius, G.; Obeid, R.; Schwinté, P.; Hemmerlé, J.; Frisch, B.; Schaaf, P.; Voegel, J.-C.; Senger, B.; Picart, C. (Langmuir, 2006)

(untitled) - Schneider, A.; Richert, L.; Francius, G.; Voegel, J.-C.; Picart, C. (Biomed. Mater., 2007)

(untitled) - Weisenhorn, A. L.; Khorsandi, M.; Kasas, S.; Gotzos, V.; Butt, H.-J. (Nanotechnology, 1993)

(untitled) - Li, X.; Logan, B. E. (Langmuir, 2004)

(untitled) - Considine, R. F.; Dixon, D. R.; Drummond, C. J. (Water Res., 2002)

(untitled) - Mathur, A. B.; Collinsworth, A. M.; Reichert, W. M.; Kraus, W. E.; Truskey, G. A. (J. Biomech., 2001)

(untitled) - Moreno-Flores, S.; Benitez, R.; Vivanco, M. d.; Toca-Herrera, J. L. (Nanotechnology, 2010)

(untitled) - Moreno-Flores, S.; Benitez, R.; Vivanco, M. d.; Toca-Herrera, J. L. (J. Biomech., 2010)

(untitled) - Matzelle, T. R.; Ivanov, D. A.; Landwehr, D.; Heinrich, L. A.; Herkt-Bruns, C.; Reichelt, R.; Kruse, N. (J. Phys. Chem. B, 2002)

(untitled) - Matzelle, T. R.; Geuskens, G.; Kruse, N. (Macromolecules, 2003)

(untitled) - Junk, M. J. N.; Berger, R.; Jonas, U. (Langmuir, 2010)

(untitled) - Radji, S.; Alem, H.; Demoustier-Champagne, S.; Jonas, A. M.; Cuenot, S. (J. Phys. Chem. B, 2010)

(untitled) - Tagit, O.; Tomczak, N.; Vancso, G. J. (Small, 2008)

(untitled) - Hashmi, S. M.; Dufresne, E. R. (Soft Matter, 2009)

(untitled) - Burmistrova, A.; Richter, M.; Uzum, C.; von Klitzing, R. (Colloid Polym. Sci., 2011)

(untitled) - Burmistrova, A.; Richter, M.; Eisele, M.; Üzüm, C.; von Klitzing, R. (Polymers, 2011)

(untitled) - Picart, C.; Senger, B.; Sengupta, K.; Dubreuil, F.; Fery, A. (Colloids Surf., A, 2007)

(untitled) - Boudou, T.; Crouzier, T.; Ren, K.; Blin, G.; Picart, C. (Adv. Mater., 2010)

(untitled) - Lo, C.-M.; Wang, H.-B.; Dembo, M.; Wang, Y. (Biophys. J., 2000)

(untitled) - Touhami, A.; Nysten, B.; Dufrêne, Y. F. (Langmuir, 2003)

(untitled) - Hurley, D. C.; Kopycinska-Müller, M.; Kos, A. B. (JOM, 2007)

(untitled) - Xu, X.; Raman, A. (J. Appl. Phys., 2007)

(untitled) - Li, J. K.; Sullan, R. M. A.; Zou, S. (Langmuir, 2011)

(untitled) - Lavalle, P.; Picart, C.; Mutterer, J.; Gergely, C.; Reiss, H.; Voegel, J.-C.; Senger, B.; Schaaf, P. (J. Phys. Chem. B, 2004)

(untitled) - von Klitzing, R. (Phys. Chem. Chem. Phys., 2006)

(untitled) - Picart, C.; Lavalle, P.; Hubert, P.; Cuisinier, F. J. G.; Decher, G.; Schaaf, P.; Voegel, J.-C. (Langmuir, 2001)

(untitled) - Picart, C.; Mutterer, J.; Richert, L.; Luo, Y.; Prestwich, G. D.; Schaaf, P.; Voegel, J.-C.; Lavalle, P. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Porcel, C.; Lavalle, P.; Ball, V.; Decher, G.; Senger, B.; Voegel, J.-C.; Schaaf, P. (Langmuir, 2006)

(untitled) - Porcel, C.; Lavalle, P.; Decher, G.; Senger, B.; Voegel, J.-C.; Schaaf, P. (Langmuir, 2007)

(untitled) - Hertz, H. (Journal für die reine und angewandte Mathematik, 1882)

(untitled) - Dimitriadis, E. K.; Horkay, F.; Maresca, J.; Kachar, B.; Chadwick, R. S. (Biophys. J., 2002)

(untitled) - Lin, D. C.; Dimitriadis, E. K.; Horkay, F. (J. Biomech. Eng., 2007)

(untitled) - Lin, D. C.; Horkay, F. (Soft Matter, 2008)

(untitled) - Lin, D. C.; Dimitriadis, E. K.; Horkay, F. (J. Biomech. Eng., 2007)

(untitled) - Attard, P. (J. Phys.: Condens. Matter, 2007)

(untitled) - Butt, H.-J.; Cappella, B.; Kappl, M. (Surf. Sci. Rep., 2005)

(untitled) - Kopycinska-Müller, M.; Geiss, R. H.; Hurley, D. C. (Ultramicroscopy, 2006)

(untitled) - Collin, D.; Lavalle, P.; Garza, J. M.; Voegel, J.-C.; Schaaf, P.; Martinoty, P. (Macromolecules, 2004)

(untitled) - Picart, C.; Sengupta, K.; Schilling, J.; Maurstad, G.; Ladam, G.; Bausch, A. R.; Sackmann, E. (J. Phys. Chem. B, 2004)

(untitled) - Attard, P. (Phys. Rev. E: Stat., Nonlinear, Soft Matter Phys., 2001)

(untitled) - Gillies, G.; Prestidge, C. A.; Attard, P. (Langmuir, 2002)

(untitled) - Radmacher, M.; Fritz, M.; Kacher, C. M.; Cleveland, J. P.; Hansma, P. K. (Biophys. J., 1996)

(untitled) - Tyrrell, J. W. G.; Attard, P. (Langmuir, 2003)

Polymer Physics - Rubinstein, M.; Colby, R. (Oxford University Press, 2003)